The Aesthetic Implications of Fichte on Feeling - Lohmann , Petra (ETHICS IN PROGRESS, 2022)
The article discusses the connection between art and emotion in Fichte’s work and its contemporary reception by the architect Karl Friedrich Schinkel. For the latter, not only selected architectural theoretical studies but also Schinkel’s ideal architectural designs are consulted. Schinkel knew Fichte personally and held him in high esteem. This is evidenced by some of Schinkel’s verbatim references to various forms of the Wissenschaftslehre and its sub-disciplines, as well as his extremely precise transcripts of lectures around the Berlin versions of the Wissenschaftslehre (around 1800). Schinkel was not only interested in the political and religious implications of Fichte’s theory of a cultural history of humankind, but his engagement with Fichte is also characterized above all by the theory of consciousness. This aspect plays a central role in the article. In recourse to the aesthetic emotion of the mind, a main concern of Fichte’s philosophy is to be placed in the horizon of architecture, which manifests itself in these questions: how does one convey a realisation in such a way that the recipient reconstructs it almost independently and it becomes a practical value for him as a criterion for his orientation in life? And furthermore – related to the research discourse on Fichte, which has only recently taken note of his aesthetic position and in particular his comments on architecture – how can this model of cognition be applied in his work from an architect’s point of view? In the investigation part on Fichte for this, first the feeling is reconstructed within the framework of the scientific-systematic philosophy as the reason of consciousness, in order to show with it the instance of the question relevant for Schinkel about the pedagogical effectiveness of a life-practical cultivating architecture. In the examination section on Schinkel, it is shown how Schinkel, in the horizon of Fichte, undertakes a determination of the relationship between feeling and ratio, with which he, for his part, establishes architecture as an instrument of cultivation.